Research on Application of the Bolt-Truss Coupling Support Technology in Roadway With Water-Rich and Soft Rock - Zhang, Jianguo; Wang, Yingwei; Qi, Xiaohan; Zhu, Tongguang (Frontiers in Earth Science, 2022)
In the process of underground energy mining, the stability of roadway support is an important guarantee. In order to study the application of the anchor cable-truss support technology in water-rich soft rock roadways, the mechanical analysis of the anchor cable-truss structure is carried out, and the surrounding rock deformation of different supporting methods is numerically simulated under the consideration of the fluid–solid coupled interaction. We observed that the anchor cable (rod)-double arch truss coupling support can control the deformation of the surrounding rock and the expansion of the plastic zone well. The maximum vault subsidence of the roadway is 0.017 m, the horizontal convergence is 0.054 m, and the deformation of floor heave is 0.02 m, which are 3.8, 16.3, and 4% of the deformation under unsupported conditions, respectively; the roadway deformation is effectively controlled. The research results have certain guiding significance for the support design of the water-rich broken soft rock roadway.